Venous Thromboembolism as an Initial Manifestation of COVID-19 in a Heart Transplant Patient - Dantas, R.C. Tourinho (J Heart Lung Transplant, 2021)
INTRODUCTION: The disease caused by the coronavirus 2019 (COVID-19) is mainly characterized by symptoms related to the upper respiratory tract associated with fever and constitutional symptoms, progressing in the most severe cases to pneumonia and severe acute respiratory syndrome (SARS). However, due to the increasing number of cases, atypical presentations have been found. Among them, thromboembolic manifestations stand out, since the virus itself seems to predispose to changes in the coagulation system. CASE REPORT: A 62-year-old male patient who underwent cardiac transplantation 6 months ago, secondary to chagasic cardiomyopathy, had pain and edema in his left foot for 1 week. Upon admission, he was eupneic, afebrile, heart rate of 96bpm, blood pressure of 120 × 70mmhg, with edema and erythema on his left foot. Chagas reactivation, cellulite or deep vein thrombosis were the diagnostic hypotheses suggested. Soft tissue ultrasound and venous doppler of the left lower limb were compatible with deep venous thrombosis and superficial thrombophlebitis. Skin lesion biopsy confirmed Chagas reactivation. Antibiotic therapy with cefazolin, full anticoagulation with enoxaparin and treatment with benzonidazole were introduced. In the second day of hospitalization, patient presented myalgia and dry cough, in addition to an increased C-reactive protein and multiple ground-glass opacities on computed tomography of the chest, suggestive of COVID-19. This finding was corroborated by a positive result of RT-PCR for SARS-COV2. The patient evolved with SARS, requiring progressive use of vasoactive drugs, mechanical ventilation and pronation. SUMMARY: It is currently known that COVID-19 increases the risk of thromboembolic events, especially in hospitalized patients, reaching an incidence of 25%, even in the presence of effective prophylaxis. Several mechanisms have been proposed for this association, but not with robust evidence. Despite these increased cases, there are no reports in the literature of initial presentation with a thromboembolic event in a heart transplant patient, emphasizing the importance of clinical suspicion and appropriate investigation.